(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
In this article, theoretical studies of the metal structure of a weight-checking wagon are carried out, which, first of all, include the development of a calculated finite element model of the body of a weight-checking wagon and conducting studies of the stress-strain state of the main load-bearing elements of the body of a weight-checking wagon under the action of operational loads on them. When carrying out strength calculations of the metal structure of the weight–checking wagon, the wall thickness will be taken into account its reduction by the value of the average wear value, thereby it will be determined whether the design of the weight-checking wagon with existing wear will withstand the loads required by the norms.